Methodology for Analysis of Solid Oxide Cells via Raman Spectroscopy. (2nd June 2015) - Manerova, Jevgenija; Call, Ann V; Sinclair, Derek C; Elder, Rachael H
Abstract : Solid oxide cells (SOCs) are highly efficient electrochemical energy conversion devices capable of operating in both fuel cell and electrolysis modes. The operating temperatures of SOCs (500 – 800 °C, for IT-SOCs) create opportunities for direct utilisation of a wide variety of reactants, including low-grade fuels such as biogas, however, in-situ characterisation of evolving electrode morphologies and compositions is challenging. The design of an optically accessible experimental setup is presented alongside methodology for obtaining and interpreting in-situ Raman spectroscopic measurements. Raman spectroscopy is a valuable analytical tool for in operando monitoring of both solid oxide electrolysis (SOEC) and fuel cells (SOFC). Molecular species adsorbed on the surface can be identified, thus providing direct insight into reaction intermediates, material phase transformations and the presence of contaminants and poisons, such as carbon, chromium, sulphur and silica. Raman spectroscopic evidence of carbon deposition during CO2 electrolysis is discussed.